Peningkatan Tumbuh Kembang Bayi Melalui Pijat Bayi Di Posyandu Wijaya Kusuma Tangkerang Tengah pekanbaru - livamaita liva (Jurnal Pengabdian Kesehatan Komunitas, 2021)
Background: One of the causes of weight problems in babies is a decreased in the baby’s appetite. Thus, to increase and maintain the baby's weight are required stimulation and stimulation in the form of massage on the baby's body (Roesli, 2013). This activity is an effort to increase the mother's knowledge about baby growth and development through baby massage at the Posyandu Wijaya Kusuma. Partner issues have never been given baby massage training. The purpose of community service is to provide counseling on baby growth and development and baby massage training. Method: Participants in counseling and baby massage practices are mothers who have babies and cadre mothers where service activities are carried out on Sunday, July 26, 2020 at 1.00 pm at the house of RT 01 Central Tangkerang Village. Results: 17 participants were asked questions about baby growth and baby massage, and almost all participants answered had never known about baby’s growth and massage. Baby massage training was given to participants by giving each participant a doll to be used as a practice tool, and participants were following videos and instructions in massage. As a result, one of the participants was randomly assigned to re-practice baby massage with the guidance of the instructor. In conclusion: The implementation of baby massage training runs successfully, the cadre mothers and mothers who have babies participate actively and enthusiastically in the implementation of the training, so that the trainees could know and practice their own baby massage with guidance. ABSTRAK Latar belakang: Salah satu penyebab permasalahan berat badan pada bayi adalah nafsu makan bayi yang turun. Dengan demikian untuk meningkatkan dan mempertahankan berat badan bayi diperlukan rangsangan dan stimulasi berupa pijatan pada tubuh bayi (Roesli, 2013). Kegiatan ini merupakan upaya untuk meningkatakan pengetahuan ibu tentang Tumbuh kembang bayi melalui pijat bayi di Posyandu Wijaya Kusuma. Permasalahan mitra belum pernah diberikan pelatihan pijat bayi. Tujuan pengabdian masyarakat: Memberikan peyuluhan Tumbuh kembang bayi dan pelatihan pijat bayi. Metode : Penyuluhan dan praktik pijat bayi. Hasil: Kegiatan pengabdian dilakukan pada hari Minggu tanggal 26 Juli 2020 Pukul 13.00 Wib di Rumah RT 01 Kelurahan tangkerang Tengah diperoleh sebelum diberikan penyuluhan dan pelatihan peserta diberikan pertanyaan mengenai Tumbuh kembang bayi dan pijat bayi dan didapatkan hampir seluruh peserta menjawab belum pernah tahu tentang tumbuh kembang dan belum tahu tentang pijat bayi. Pelatihan pijat bayi diberikan kepada peserta dengan memberikan masing2 peserta boneka untuk dijadikan alat praktik dan peserta mengikuti video dan intruktur dalam pemijatan. Hasil pelatihan ditunjuk salah seorang peserta secara acak untuk mempraktekkan kembali pijat bayi dengan bimbingan instruktur. Simpulan: Pelaksanaan pelatihan pijat bayi berjalan dengan sukses, ibu kader dan ibu yang memiliki bayi ikut aktif dan antusias dalam pelaksanaan pelatihan, sehingga peserta pelatihan dapat mengetahui dan mempraktekkan sendiri pijat bayi dengan bimbingan.